2017
DOI: 10.1016/j.ifset.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasound application on both the osmotic pretreatment and subsequent convective drying of pineapple (Ananas comosus)

Abstract: Correa, J.; Rasía, M.; Mulet Pons, A.; Carcel Carrión, JA. (2017). Influence of ultrasound application on both the osmotic pretreatment and subsequent convective drying of pineapple (Ananas comosus). AbstractUltrasound application represents an alternative means of improving heat and mass transfer. This study explored the combined application of ultrasound (US) during both the osmotic dehydration (OD) pretreatment and the convective drying of pineapple. For that purpose, fresh and pretreated samples (20 or 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 41 publications
5
43
0
3
Order By: Relevance
“…Prosapio and Norton (2017) reported that the application of OD pretreatment prior to oven and freeze drying lessened the drying time and preserved the bioactive compounds and the nutritional properties. Osmotic dehydration has been used as pretreatment process for various crops such as guavas (Vieira, Pereira, & Hubinger, 2012), pineapple (Corrêa, Rasia, Mulet, & Cárcel, 2017), and carrot (Kaur & Sogi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prosapio and Norton (2017) reported that the application of OD pretreatment prior to oven and freeze drying lessened the drying time and preserved the bioactive compounds and the nutritional properties. Osmotic dehydration has been used as pretreatment process for various crops such as guavas (Vieira, Pereira, & Hubinger, 2012), pineapple (Corrêa, Rasia, Mulet, & Cárcel, 2017), and carrot (Kaur & Sogi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in air temperature resulted in larger driving forces for heat transfer and water evaporation [24]. This effect was observed by [5,10] during the drying process of pineapple and banana, respectively. The use of reduced pressures in vacuum drying improves the drying time (C80 and V80).…”
Section: Experimental Dryingmentioning
confidence: 98%
“…Besides reducing water activity, drying also reduces the volume and weight of products, leading to lower costs of packaging, transport and storage [5]. Convective drying is the most common and easily utilized drying method [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Перспективными направлениями в области создания ресурсосберегающих технологий в сушке растительного сырья являются инфракрасная сушка и сушка в поле действия ультразвука. Анализируя труды российских и зарубежных ученых в данной области, авторами статьи было решено использовать ультразвук для достижения цели исследования, а именно уменьшение потери витаминов за счет применения современных ультразвуковых технологий, позволяющих снизить температурный режим и сократить время сушки, а также улучшить качественные показатели высушенного продукта [4,11,[13][14][15][16][17][18][19][20].…”
Section: Introductionunclassified